A safe lithium mimetic? The inositol depletion hypothesis rescues an experimental drug for bipolar disorder - Churchill, G; Singh, N; Vasudevan, S (2013)
Vincent Van Gogh painted for just 10 years, but produced over 2000 works of art in periods of intense productivity and creativity. However, during these creative periods, his personal life was one of chaos with poor and impulsive decisions relating to finance, career, business, substance abuse, sexuality and romance (sending his severed ear to the object of his affection), and between these periods he was institutionalized with crushing depressions and he eventually took his own life. It is likely that he suffered from what we now know as bipolar disorder. Insight into mood is not easily conveyed, but we can get a sense of Van Gogh's mood extremes from two of his paintings, both with the theme of a starry night, but one suggesting exuberant mania and one gloomy depression. Surprisingly, the best treatment for bipolar disorder still remains the one first discovered over 60 years ago: the cation lithium. Nevertheless, lithium's side effects and toxicity have spurred the search for a replacement. © 2013 Biochemical Society.